How Conceptual Art Challenges Copyright’s Notions of Authorial Control and Creativity - Buccafusco, Christopher (The Columbia Journal of Law & the Arts, 2020)
Here’s the basic argument: that to the extent that someone exerts too little control or that there is too much unpredictability about the way in which the work will be produced, then that person is at risk of being declared not an author of the work. Copyright law looks for control and predictability, and if there’s not enough of either, then copyright law and the Copyright Office may conclude that the creator is not an “author” of the work. On the other hand, to the extent that there is too much control or too much predictability, then authors run the risk of being told that their work is not creative. In fact, the strategy for an author is to balance these sorts of competing requirements: to exert control over the ultimate product, but not so much control that you risk losing the opportunity for creative expression.